The Effect of Big Data Analytics on Predictive Policing: The Mediation Role of Crisis Management - Alkhazraji, Ibrahim Abdulla Mohammad Aldallal; Yahya, Mohd Yamani bin (RGSA : Revista de Gestão Social e Ambiental, 2024)
Objective: The objective of this study is to evaluate the impact of big data analytics (BDA) on predictive policing, particularly examining the mediating role of crisis management in this relationship.